A model of reversible inhibitors in the gastric H+/K+-ATPase binding site determined by rotational echo double resonance NMR. - Watts, J; Watts, A; Middleton, D (2001)
Several close analogues of the noncovalent H(+)/K(+)-ATPase inhibitor SCH28080 (2-methyl-3-cyanomethyl-8-(phenylmethoxy)imidazo[1,2-a]pyridine) have been screened for activity and examined in the pharmacological site of action by solid-state NMR spectroscopy. TMPIP, the 1,2,3-trimethyl analogue of SCH28080, and variants of TMPIP containing fluorine in the phenylmethoxy ring exhibited IC(50) values for porcine H(+)/K(+)-ATPase inhibition falling in the sub-10 microm range. Deuterium NMR spectra of a (2)H-labeled inhibitor titrated into H(+)/K(+)-ATPase membranes revealed that 80-100% of inhibitor was bound to the protein, and K(+)-competition (2)H NMR experiments confirmed that the inhibitor lay within the active site. The active binding conformation of the pentafluorophenylmethoxy analogue of TMPIP was determined from (13)C-(19)F dipolar coupling measurements using the cross-polarization magic angle spinning NMR method, REDOR. It was found that the inhibitor adopts an energetically favorable extended conformation falling between fully planar and partially bowed extremes. These findings allowed a model to be proposed for the binding of this inhibitor to H(+)/K(+)-ATPase based on the results of independent site-directed mutagenesis studies. In the model, the partially bowed inhibitor interacts with Phe(126) close to the N-terminal membrane spanning helix M1 and residues in the extracellular loop bridging membrane helices M5 and M6 and is flanked by residues in M4.